Approach and management of children with raised intracranial pressure - Ramachandran Rameshkumar; Arun Bansal (Wolters Kluwer Medknow Publications, 2015)
Raised intracranial pressin e (ICP, > 20 mm Hg) is often seen in children with acute brain injury of various etiologies and often complicates the clinical picture and management; it may progress into herniation syndrome and death. The volume of intracranial compartments is tightly regulated, and cerebral blood flow (CBF) is kept constant despite fluctuations in systemic blood pressure by [4]cerebral autoregulation'. Symptoms and signs of raised ICP are neither sufficiently sensitive nor specific; hence identifying patients at risk of developing raised ICP is a crucial for preventing seonday brain injury Persistent elevation of ICP above 20 mm Hg for greater than 5 minutes in a patient who is not being stimulated should be treated immediately Immediate goal of management is to prevent/reverse herniation and to maintain good cerebral perfusion pressure. The therapeutic measures include stabilization of airway, breathing and circulation, along with neutral neck position, head end elevation by 30°, adequate sedation and analgesia, minimal stimulation, and hyperosmolar therapy (mannitol or 3% saline). Short-term hyperventilation, to achieve PC02-30 inin Hg, using bag ventilation can be resorted to if impending herniation is suspected. CPP targeted therapy (targeting CPP > 60 mm Hg) is associated with better clinical outcome. Decompressive craniotomy may improve the outcome in raised ICP unresponsive to medical treatment. However, indiscriminate use of this surgery is not advised as the procedine and subsequent cranioplasty are associated with a number of complications.